THE EFFECT OF MUTATION AND PROMOTION ON EMPLOYEE WORK PERFORMANCE AT BANK BRI, JAYABAYA UNIT BRANCH, CENTRAL JAKARTA - Wulandari, Satia; Sri Wahyuningsih; Meirna Milisani (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2025)
This research has a quantitative approach, descriptive and associative type, the population in this research is 31 employees of Bank BRI Jayabaya Unit Branch, Central Jakarta. The sampling technique used total sampling. The regression value (tcount) for variable X1 (Mutation) is 3,802, while the ttable value for N = 31 is 2.041. So 3,802 > 2.041, it can be concluded that partially the Mutation variable does have a positive influence on employee work performance. Probability value (significance) = 0.005. So the probability of 0.005 is below 0.05. Thus, H0 is rejected and Ha is accepted, it can be concluded that there is a positive and significant influence between variable X1 and variable Y, because the probability value is smaller than 0.05. The regression value (tcount) for variable X2 (Promotion) is 3,298, ttable value for N = 31 is 2.041. So 3,298 > 2.041, it can be concluded that partially the Promotion variable does have a positive influence on employee work performance Thus, H0 is rejected and Ha is accepted, and it can be concluded that there is a positive and significant influence between variable X2 and variable Y, because the probability value is smaller than 0.05. The calculated F value is 20,254 which is greater than the F table of 2.91 with a significant level of 0.000 because 0.000 < 0.05, so it can be said that the Mutation variable (X1) and the Promotion variable (X2) together have an influence on the employee work performance variable. (Y). Meanwhile, the result of the R2 (R Square) value is 0.591. This shows that 59.1% of simultaneous transfers and promotions have a positive effect on employee work performance, while the remaining 40.9% have an effect on other factors not examined in this research.